Genetic determinant of metabolic syndrome – a review - Nagarajan, Haritha; Gopalakrishnan S., Santhini (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Metabolic syndrome is a pathological condition that is a combination of insulin resistance, hypertension, dyslipidemia, and abdominal obesity. Every metabolic syndrome trait has an estimated hereditary factor greater than fifty percent. Many mutations related to distinct traits have been successfully identified through genetic studies. With respect to the advancements in our knowledge of the genetics of obesity, it is a major contributor to metabolic syndrome. Metabolic syndrome is associated with many diseases and is closely related to overweight / obesity and lack of activity. Genetic predisposition also plays an important role in it. Therefore, lifestyle modification is the initial and main intervention that can be implemented for such a population. This review pinpoints the literature on the definition of metabolic syndrome, epidemiology, pathogenesis, and its gene polymorphism and treatment approach comprising metabolic syndrome. Material and methods. The literature review was carried out using databases such as PubMed, Scopus, Google Scholar and the Web of Science for studies looking into metabolic syndrome and its complications. This review provides a comprehensive analysis of the role of genetic and lifestyle changes in the development of metabolic syndrome. Analysis of the literature. Metabolic syndrome is a collection of diseases that include lower levels of high-density lipoprotein (HDL), increased triglyceride levels (TG), high blood pressure, more waist circumference, and elevated fasting blood glucose. It is closely related to overweight / obesity and lack of activity. Genetic predisposition also plays an important role in it. So lifestyle modification is the initial and main intervention that can be implemented for this population. Conclusion. Genetic, lifestyle changes, and other environmental changes contribute to the development of metabolic syndrome. Metabolic syndrome leads to many health issues; for a better healthy outcome, lifestyle modifications such as healthy dietary habits, following regular physical activity, quitting smoking and alcohol, balanced weight, stress management are required.